Increased consumption of ultra-processed foods and worse diet quality in colorectal cancer patients after colostomy: A prospective study - Arenamoline Xavier Duarte; Karine de Almeida Silva; Isabela Borges Ferreira; Cristiana Araújo Gontijo; Geórgia das Graças Pena (PLoS ONE, 2025)
Colorectal cancer (CRC) is commonly treated with intestinal resections that lead to colostomy, which can influence changes in eating habits. This study aimed to analyze energy and nutrient intake, diet quality, and food consumption based on the processing level in CRC patients after colostomy. A prospective study was carried out at three time points (T0–recent colostomy, T1–3 months after colostomy, and T2-6 months after colostomy). Food intake was assessed by 24-hour dietary recall. Macro-micronutrient consumption, the Brazilian Healthy Eating Index-Revised (BHEI-R), and food consumption according to processing level by NOVA classification (raw or minimally processed, processed, and ultra-processed foods) were estimated. Generalized estimating equations were used to compare the food intake variables with time points. Of the 46 patients, 52.2% were women, and the mean age was 60.6±12.2 years old. There was a change in food consumption over time, with an increase in energy consumption (kcal and kcal/kg), lipids, and sodium, in addition to a reduction in some nutrients such as protein (g and g/kg), fiber, vitamin B1 and C and phosphorus. Regarding the key outcomes, BHEI-R and NOVA classification showed a poor diet quality with a reduction in total index (p = 0.022), raw food (p = 0.001), total fruits, and whole fruit consumption (p = 0.001), and an increase in sodium (p = 0.001) at 3 and/or 6 months after colostomy concomitant an increase in ultra-processed food (p = 0.015). Nutritional counseling is essential in care, effective eating changes habits improvement of symptoms and nutritional status, besides avoiding potential cancer recurrence.